The Legitimation of international organisations : examining the identity of the communities that grant legitimacy - Symons, Jonathan (2011)
Rejects the argument that international organisations must gain legitimacy among all subject social constituencies within the political realm of action. Argues instead that the importance of legitimacy within a particular constituency is a variable, a "legitimacy nexus" and outlines the factors that are hypothesised to contribute to calibrating this nexus.